Evaluation of Online Learning in Students' Understanding of Mathematics Learning - Puspita, Nadra (EDUCTUM: Journal Research, 2023)
Education is a conscious effort to create a cultural heritage from one generation to the next. Education is one of the human efforts to foster and develop potential - potential with values - values that exist in society. Education creates an atmosphere and learning process so that students are able to recognize their potential, self-control, character, intelligence, morality, and actively develop the knowledge needed for themselves and society according to the law. Education is also referred to as teaching and learning activities carried out by teachers and students in classroom interactions, because in general teachers must teach and everyone has an obligation to teach. In the teaching and learning process at school, teachers play an important role in teaching and guiding students, especially in learning mathematics. As a result of covid-19, the learning process becomes inefficient and face-to-face interaction between teachers and students can no longer be done. Therefore, students are required to learn from home by using online learning.